PHYSICAL, CHEMICAL, AND BIOLOGICAL SOIL ATTRIBUTES UNDER ANALOG AGROFORESTRY SYSTEM AND PASTURE SITES - Camara, Rodrigo; Silva, Camila Santos da; Santos, Gilsonley Lopes dos; Aguiar, Gabriel Santos; Pereira, Marcos Gervasio Gervasio; Silva, Cristiane Figueira; Silva, Eliane Maria Ribeiro (Floresta, 2019)
Analog agroforestry system uses native tree species to improve soil conditions and the microclimate of degraded areas. This study aimed to assess the impact of analog agroforestry on physical, chemical, and biological soil attributes. We tested the hypothesis that some of these attributes can be used as indicators of soil quality improvement compared to a managed pasture area. Two experimental sites were selected, an analog agroforestry site and a pasture site. In October 2016 (end of the dry season), soil samples were collected from the 0–5 and 5–10 cm depths and the soil fauna community was sampled using pitfall traps. The analog agroforestry system led to increased total abundance, total richness, mean richness, evenness, and diversity of the soil fauna community as well as higher gravimetric soil moisture, sand content, pH, calcium, magnesium, and sum of exchangeable bases, which are good indicators of soil quality. Adults of Coleoptera, Diptera, Gastropoda, Hymenoptera, Isopoda, Lepidoptera, Poduromorpha, Symphypleona, Pseudoscorpionida, Lepidoptera and larvae of Coleoptera, Diptera, Lepidoptera, and Neuroptera were the most abundant taxonomic groups in the analog agroforestry system.